COMPARATIVE ANALYSIS OF ORGANIC AND INORGANIC RICE FARMING (CASE STUDY OF THE MASSUMPULOLOE SATU FARMERS GROUP) - Fajriah; Iranita Haryono; Astrini Padapi (Universitas Muhammadiyah Makassar, 2026)
The rice farming system in Indonesia is generally divided into two main approaches, namely organic and inorganic systems, which have differences in the use of production inputs, cost structures, and levels of profit generated. This research was conducted at the Massumpuloloe Satu Farmer Group in Bulo Village, which is under the guidance of P4S Bukit Melintang and has implemented both farming systems. The purpose of the study was to analyze the comparison of production costs, revenues, and profitability levels between organic and inorganic rice farming. The research method used a descriptive quantitative approach with a survey technique through questionnaires and interviews with respondents who were selected purposively, namely having the same land area of ​​​​5 Ha. The results showed that organic rice farming had a lower total production cost of Rp 7,057,690 compared to inorganic at Rp 16,531,625, and generated higher revenues of Rp 135,150,000 compared to Rp 95,810,000 in the inorganic system. The profitability of organic farming is also higher, with an ROA of 14.17%, a R/C Ratio of 19.15, an NPM of 94.78%, and a GPM of 94.78%, as well as lower production and price break-even points compared to inorganic farming. Overall, organic rice farming demonstrates better cost efficiency, higher profit margins, and lower risk of loss, making it a potentially more profitable and sustainable alternative farming system.